Some notes on indigenous law and special indigenous jurisdiction - Iglesias, María del Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The recognition of the rights of indigenous peoples leads, in its necessary evolution, to the recognition of a particular indigenous jurisdiction, understood as the power to administer justice in the different branches of law, following ancestral uses and customs, their own rules and procedures and, in short, a certain legislation. It implies that, together with state law, there is a kind of exceptionality when specific requirements are met, which these lines address. Its application reveals problems relating to jurisdiction and the applicable law, and the recognition of the decisions issued in a particular venue; an exception that has its objective limits in the affectation of the Constitution, human rights and public order. All this is based on the recognition of legal pluralism, ethnic plurality, multiculturalism, and cultural identification and self-determination of peoples understood within the respect for the sovereignty and integrity of the State.